The effectiveness of a digital learning environment in developing the mathematical achievement of students with hearing impairment during the period of education disorder (COVID- 19) - El- Gohary, Hala Khairy Abdel- Ghany (Journal of Educational and Psychological Sciences, 2021)
The current research aimed at measure the effectiveness of a digital learning environment in developing the mathematical achievement of students with hearing impairment during the period of education disorder (COVID- 19) in the middle stage, and the researcher used an achievement test that is repeated three weeks after the application to know the effectiveness of the learning environment in the development of mathematical achievement of Intermediate school students, and the researcher used the descriptive approach to address the theoretical framework related to the research from previous studies and others, and the quasi- experimental approach to measure the effectiveness of the independent variable, the digital learning environment on the variables dependent on mathematical achievement, and the study sample consisted of (24) pupils and his student in the intermediate stage in Wadi Al- Dawasir governorate divided To two experimental and control groups, the researcher also used the Mann- Whitney test to calculate the difference between the mean scores of the experimental and control group students in the post application of the mathematical achievement test and calculate the effectiveness of the gain ratio. The most important results of the study were the presence of a statistically significant difference at the level of significance (α ≤ 0.05 (between the mean scores of the experimental group and the control group students in the post- mathematical achievement test, and this means that the experimental group students who learned through the digital learning environment increased their mathematical achievement than the pupils The control group who learned in the traditional way, and recommends the researcher to employ different digital learning environments to teach many concepts to people with hearing disabilities during the different stages of education. And setting technical and educational standards for these environments, as the researcher proposes to train teachers of schools with hearing disabilities on modern strategies and technologies in the classroom.